Developing Creative Fashion Industry in Central Java Province - Agus Budi Santosa; Agung Nusantara; Sri Nawatmi (Trunojoyo University of Madura, 2022)
The advantage of the fashion industry are contributing to creating a workforce and creating high values of various commodities. The growth of the industrial sector becomes the mainstay of local government to increase Indonesia’s economy as one of the most dominant economic sectors. This article will analyze strategies and policies to develop the fashion industry with SWOT analysis. The research results showed the strengths aspects, like supportive local sources, cultural wealth, and available facilities and infrastructures. The supporting of opportunity aspects is the open chances of domestic and foreign markets and government concern and support. Developing human resources competencies, developing promotion as well as fashion product marketing, and cost aspects were conducted to develop the creative industry.